Acquired erythropoietic protoporphyria secondary to myelodysplastic syndrome: from mythology to oncologyAcquired Erythropoietic Protoporphyria Secondary to Myelodysplastic Syndrome: From Mythology to Oncology - Mirjana Urosevic-Maiwald; Jivko Kamarachev; Christoph Renner; Anna-Elisabeth Minder (Medical Journals Sweden, 2024)
Abstract is missing (Short communication)